2010
DOI: 10.1002/ajmg.b.31151
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of candidate regions for bipolar disorder provides strong evidence for susceptibility loci on chromosomes 7q

Abstract: Genomewide scans of bipolar disorder (BP) have not produced consistent linkage findings. Follow-up studies using enlarged samples and enhanced marker density can bolster or refute claims of linkage and pave the way to gene discovery. We conducted linkage and association analyses, using a ~3-cM density map of 10 candidate regions, in a large BP pedigree sample (865 individuals from 56 pedigrees). The candidate regions were identified in a previous 10-cM genome-wide scan using a subset of this sample (373 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Results include, but are not limited to, circadian rhythms (e.g., aryl hydrocarbon receptor nuclear translocator‐like BmaL1 (ARNTL) and RAR‐related orphan receptor B (RORB), neuronal development (e.g., neurotrophic factors and DISC1) , calcium metabolism (e.g., CACNA1C and RASGRP1) , monoamine metabolism (e.g., TPH1 A218C) , mitochondrial function (e.g., POLGI) and cell survival . Notwithstanding, effect sizes for most susceptibility genes are low, results are often inconsistent, and discriminant power is insufficient for clinical utility .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results include, but are not limited to, circadian rhythms (e.g., aryl hydrocarbon receptor nuclear translocator‐like BmaL1 (ARNTL) and RAR‐related orphan receptor B (RORB), neuronal development (e.g., neurotrophic factors and DISC1) , calcium metabolism (e.g., CACNA1C and RASGRP1) , monoamine metabolism (e.g., TPH1 A218C) , mitochondrial function (e.g., POLGI) and cell survival . Notwithstanding, effect sizes for most susceptibility genes are low, results are often inconsistent, and discriminant power is insufficient for clinical utility .…”
Section: Resultsmentioning
confidence: 99%
“…Several investigations have reported structural, functional, and neurochemical abnormalities in the central nervous system (CNS) of pediatric populations with BD and those identified as at risk . Volumetric studies have reported abnormalities in several regions including, but not limited to, smaller cerebral volumes , enlargement of the striatum, and smaller and larger amygdala volumes .…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the GCR locus 5q31 is associated to hypertension99 and linked to bipolar disorder 100. The MCR locus chromosome 4q31.1-31.2 is linked to T2D and MetS101 and to bipolar disorder 102105106115…”
Section: Implication Of the Hpa Axis And Related Candidate Genes In Tmentioning
confidence: 99%
“… 100 The MCR locus chromosome 4q31.1-31.2 is linked to T2D and MetS 101 and to bipolar disorder. 102 105 MCR and GCR variants affect coping style and depression vulnerability, antidepressants response, stress, and depression endocrine response. 106 115 MCR expression is increased in the hypothalamus of diabetic rats 116 and MCR is linked to blood pressure.…”
Section: Implication Of the Hpa Axis And Related Candidate Genes In Tmentioning
confidence: 99%